2019
DOI: 10.1038/s41467-019-10904-8
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate receptor 3 in the medial prefrontal cortex promotes stress resilience by reducing inflammatory processes

Abstract: Stress can promote the development of psychiatric disorders, though some individuals are more vulnerable to stress compared to others who are more resilient. Here we show that the sphingosine-1-phosphate receptor 3 (S1PR3) in the medial prefrontal cortex (mPFC) of rats regulates resilience to chronic social defeat stress. S1PR3 expression is elevated in the mPFC of resilient compared to vulnerable and control rats. Virally-mediated over-expression of S1PR3 in the mPFC produces a resilient phenotype whereas its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 65 publications
5
73
0
Order By: Relevance
“…The coping response of experimental animals exposed to stress has been used in other studies to distinguish between resilient and vulnerable individuals. For example, male rats were classified as having an active or passive coping strategy according to their latency of submission (Wood et al, 2010(Wood et al, , 2013Pearson-Leary et al, 2017;Grafe et al, 2018;Corbett et al, 2019) and the index of flee behavior in a social interaction test performed after RSD has also been applied to mice (Henriques-Alves and Queiroz, 2016).…”
Section: Resilience To the Long-term Effects Of Rsd On Cocaine Cpp Ismentioning
confidence: 99%
“…The coping response of experimental animals exposed to stress has been used in other studies to distinguish between resilient and vulnerable individuals. For example, male rats were classified as having an active or passive coping strategy according to their latency of submission (Wood et al, 2010(Wood et al, , 2013Pearson-Leary et al, 2017;Grafe et al, 2018;Corbett et al, 2019) and the index of flee behavior in a social interaction test performed after RSD has also been applied to mice (Henriques-Alves and Queiroz, 2016).…”
Section: Resilience To the Long-term Effects Of Rsd On Cocaine Cpp Ismentioning
confidence: 99%
“…On hippocampal slices, it has been shown that S1PR1 signaling influences NMDAR properties [101]. Similarly, ablation of S1PR3 impairs neuronal hippocampal excitability in vitro [102] and reduces inflammatory processes in medial prefrontal cortex in mice [103], both areas involved in pain processing [104]. However, more in-depth studies on S1P signaling also need to be addressed towards other brain structures responsible for pain modulation, such as cingulate cortex, thalamus, periaqueductal grey, and rostroventral medulla.…”
Section: S1p Axis In Central Sensitizationmentioning
confidence: 99%
“…Research reports show the impact of chronic unpredictable stress on cellular integration and active involvement of certain brain regions such as DG, prefrontal cortex, and hippocampus [ 4 , 5 ]. The medial prefrontal cortex is an essential neural substrate helping in modulating the hypothalamic-pituitary-adrenal axis during the exposure to stressful situations [ 6 ].…”
Section: Introductionmentioning
confidence: 99%